Application of Laney control chart in assessment of microbiological quality of oral pharmaceutical filterable products (Bangladesh Journal of Scientific and Industrial Research, 2017)
Evaluation of microbiological quality of pharmaceutical product is an important criterion for safe release of the dosage form to the drug market. Monitoring of the stability of monitored characteristic attribute is crucial to judge the degree of compliance of the manufacturing processes to reproducible procedures and good manufacturing practice (GMP). Two non-sterile liquid oral products were monitored during ten months of study for their microbiological stability characteristics using control charts. Since total viable count (TVC) results did not follow any distribution type, the application of Laney U? chart was found to be the best approach in such instances using relevant statistical software packages. The results of TVC for both products failed to follow the closest distribution in distribution fitting test at ? = 0.05. Interestingly, both products demonstrated several spots of out-of-control (OOC) states, although none of their batches showed out-of-specification (OOS) results. These OOC conditions require further investigations in order to provide corrective/preventive actions for improvement of bioburden stability of the manufactured pharmaceuticals. Accordingly, Laney attribute control chart may be regarded as very handy tool to evaluate microbiological characteristic of pharmaceutical dosage form, when results show significant over-dispersion or under-dispersion pattern in data distribution.Bangladesh J. Sci. Ind. Res. 52(3), 239-246, 2017